Traditional restaurant managers' use of sensory marketing to maintain customer satisfaction: Findings from PLS-SEM and fsQCA - Pantas H. Silaban; Wen-Kuo Chen; Ixora Javanisa Eunike; Andri Dayarana K. Silalahi (Cogent Business & Management, 2023)
The sensory experience is the initial step in creating memorable dining experiences for consumers in traditional restaurants. However, the question remains as to how managers should best combine the five senses to satisfy customers. More research is needed to determine how sensory cues can be used in marketing strategies. By applying five sensory marketing to traditional restaurants, this study proposes a model for satisfying customers. In addition, it aims to leverage methodologies that ultimately lead to customer satisfaction based on sensory marketing that can serve as guidelines for restaurant managers. The study hypotheses were tested on a sample of 525 Indonesians who dined at traditional restaurants. Data analysis was conducted using structural equation modelling with Smart-PLS 4.0 and fuzzy set qualitative comparative analysis (QCA) 3.0. The results indicated that olfaction and haptics are significant factors in customer satisfaction, whereas visual, taste, and auditory are not. According to the QCA findings, two configurations were associated with high satisfaction outcomes, while two others were associated with low satisfaction outcomes. As a theoretical and managerial contribution, this study provides guidance to scholars and managers interested in improving satisfaction in traditional restaurants through sensory marketing techniques.
Keywords: 650; asymmetrical analysis; consumer behaviour; customer satisfaction; destination marketing; hospitality marketing; managers; sensory marketing; strategic management; traditional restaurants